Jesus, the Holder of the Seven Stars in His Right Hand: An Examination of Rev 1:16a in Light of Numismatic Evidence - Lee, Sanghwan (Novum Testamentum, 2022)
In Rev 1:16a, Jesus is portrayed as holding the seven stars in his right hand. The immediate context interprets this imagery as Jesus’s exercising his sovereignty over the seven angels of the seven churches (v. 20). This article suggests that a secondary interpretation is possible in light of numismatic evidence and the larger context of Revelation. According to this reading, the depiction of Jesus in Rev 1:16a functions as a literary device that subverts the message embedded in the Divvs Caesar coin types—a message that promotes the imperial power. By portraying Jesus as the holder of the seven stars in his right hand, the author of Revelation places Jesus far above the imperial power, claiming that Jesus is the ruler par excellence whose sovereignty extends to both the terrestrial and celestial realms.